Strategia w działalności małych przedsiębiorstw - metodyka i wyniki badań empirycznych - Ćwik, Krzysztof (Strategy in small enterprises' operating - presentation of empirical research outcome, 2006)
The paper presents empirical research of hypothesis, which says, that the majority of small enterprises has strategy. The article includes theoretical background of this hypothesis, as well as methods and results of its empirical verifications.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (4); 2006; nr 1114, s. 274-283